Contemporary Concept of Welfare State - Ohanyan , V. (Bulletin of Yerevan University C: Jurisprudence, 2018)
Analysis of the challenges and conditions of functioning of welfare state nowadays reveals the great need to revisit the nature and goals of the welfare state based on the principles of leaving no one behind, chance to equal start, equal opportunities, investment in human capital, leveraging social capital and relationship with civil society, reform of the concept and system of social protection.
Keywords: welfare state, social justice, equal start, equal opportunities, human capital, social capital, sustainable development goals